2021
DOI: 10.3390/cancers13040648
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutations and the 8th Edition TNM Classification in Predicting the Survival of Thyroid Cancer Patients

Abstract: Our research group has previously shown that the presence of TERT promoter mutations is an independent prognostic factor, by applying the TERT mutation status to the variables of the AJCC 7th edition. This study aimed to determine if TERT mutations could be independent predictors of thyroid cancer-specific mortality based on the AJCC TNM 8th edition, with long-term follow-up. This was a retrospective study of 393 patients with pathologically confirmed differentiated thyroid carcinoma (DTC) after thyroidectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Therefore, it is believed that TERT promoter mutations play an important role in death from DTC. In a previous study, we demonstrated that TERT promoter mutations act as an independent poor prognostic factor with the TERT promoter mutational status based on TNM-8 in a cohort of patients with DTC [14].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, it is believed that TERT promoter mutations play an important role in death from DTC. In a previous study, we demonstrated that TERT promoter mutations act as an independent poor prognostic factor with the TERT promoter mutational status based on TNM-8 in a cohort of patients with DTC [14].…”
Section: Discussionmentioning
confidence: 90%
“…The same dataset was used in the previous study [14]. In brief, from October 1994 to December 2004, a total of 393 patients with pathologically confirmed DTC, 327 with papillary thyroid cancer (PTC) and 66 with FTC, including Hurthle cell carcinoma, were enrolled in this study after thyroidectomy and neck dissection.…”
Section: Patients and Clinicopathological Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The TERT promoter mutations in combination with BRAF alterations define the most aggressive subtypes among papillary thyroid cancer patients with distance metastases, the highest recurrence, and mortality 123 . In differentiated thyroid cancer, the promoter mutations define an independent prognostic factor after adjusting for risk factors described in the 8 th edition of the American Joint Committee on Cancer classification 124 .…”
Section: Impact Of Tert Promoter Mutationsmentioning
confidence: 99%
“…Although subsets of PTC patients exhibit high morbidity, the disease-specific mortality is low due to the combined efficacy of surgery and adjuvant radioactive iodine (RAI) treatment [ 2 , 3 ]. In terms of clinical characteristics known to increase the risk of recurrence, higher patient age, certain histological subtypes, increased tumor size as well as the presence of extrathyroidal extension, vascular invasion, and/or lymph node involvement are all recognized factors [ 1 , 4 , 5 ]. The v-raf murine sarcoma viral oncogene homolog gene ( BRAF ) is the most common recurrently mutated gene in PTC, with activating V600E mutations present in 50–70% of adult patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%